Symptomatic renal arteriovenous malformation before and after rupture -- endovascular and surgical approach - Lisa Meunier-Geleng; Loic Choffel; Gabriel Simon; Alexandre Frontczak; François Kleinclauss (Urology Case Reports, 2025)
Renal arteriovenous malformations are rare, with significant challenges in management due to their high-flow nature and potential serious complications. We present a case of a 78-year-old female with no significant medical history, who presented with hematuria and right-sided lumbar pain. Imaging revealed a large right renal arteriovenous malformation. Due the size and the location, a surgical approach by right nephrectomy rather than endovascular therapy was decided. Prior to surgery, the renal arteriovenous malformation ruptured into the renal excretory cavities, with a retroperitoneal aneurysm causing a large hematoma and hematuria. Emergency embolization was performed, followed by a nephrectomy the next day.